2020
DOI: 10.1002/acn3.51025
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia‐ataxia syndrome with permanent torsional nystagmus caused by ECHS1 deficiency

Abstract: Biallelic mutations in ECHS1, encoding the mitochondrial enoyl-CoA hydratase, have been associated with mitochondrial encephalopathies with basal ganglia involvement. Here, we describe a novel clinical presentation consisting of dystonia-ataxia syndrome with hearing loss and a peculiar torsional nystagmus observed in two adult siblings. The presence of a 0.9-ppm peak at MR spectroscopy analysis suggested the accumulation of branched-chain amino acids. Exome sequencing in index probands identified two ECHS1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Quality of life in these patients and their caregivers are influenced by progressive evolution. Prognosis is poor, with a short survival rate of about 70 months, but cases with neonatal deaths or adulthood survival up to 32 years have also been reported [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life in these patients and their caregivers are influenced by progressive evolution. Prognosis is poor, with a short survival rate of about 70 months, but cases with neonatal deaths or adulthood survival up to 32 years have also been reported [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic mutations have been found in the ECHS1 gene encoding the enoyl-CoA hydratase protein, and they have been associated with early onset of a Leigh-like syndrome that is characterized by the development of progressive encephalopathy and mitochondrial deficits leading to the development of optic atrophy, developmental delay, and symptoms not related to neuromuscular disorders, such as epilepsy and bilateral hearing loss [ 226 , 227 , 228 ]. Recently, ECHS1 enzyme deficiency has been associated with the development of a new symptomatology associated with dystonia-ataxia syndrome with permanent torsional nystagmus [ 214 ].…”
Section: Alterations Of Mitochondrial Enzymes Impair Neuromuscular Functionsmentioning
confidence: 99%
“…In contrast, intermediate and mild cases usually have normal laboratory values. A review of the literature 1‐4,6‐29 revealed 67 patients with most suffering the early onset presentation. Average age at death was 28.0 + 43.8 months (range 16 h to 156 months) for 27 early onset patients (age <12 months) for whom age at death was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Short Chain Enoyl Co-A Hydratase (SCEH) deficiency is a phenotypically heterogeneous disorder ranging from an early onset severe progressive Leigh-Like Syndrome with early demise 1,2 to later onset childhood movement disorders. 3,4 Early onset symptoms include hypotonia, respiratory insufficiency, global developmental delay, encephalopathy, sensorineural hearing loss, cardiomyopathy, and bilateral basal ganglia lesions. 5 Less common are the later onset mildly symptomatic patients with varied movement disorders and basal ganglia lesions.…”
Section: Introductionmentioning
confidence: 99%